A hybrid treatment system for water contaminated with pentachlorophenol: Removal performance and bacterial community composition. (October 2021) - Muhamad, Mohd Hafizuddin; Abdullah, Siti Rozaimah Sheikh; Hasan, Hassimi Abu; Bakar, Siti Nur Hatika Abu; Kurniawan, Setyo Budi; Ismail, Nur 'Izzati
Abstract: A hybrid treatment system of multimedia–sequencing batch biofilm reactor (MM-SBBR; B) and three control bioreactors (C, D, E) processing synthetic wastewater containing pentachlorophenol (PCP), were used to study the effectiveness of PCP removal and the impact of high-levels of PCP (100 mg L −1 ) on bacterial community compositions. Another MM-SBBR (A) treating real effluent of the recycled paper mill industry containing PCP was also operated and compared. The MM-SBBR (B) achieved a high chemical oxygen demand (COD), ammoniacal nitrogen (NH3 -N), and PCP removal efficiencies, reaching 97%, 93% and 99%, respectively, which were attributed to the enrichment of high PCP resistant bacteria in this reactor. It was found that the number of bacterial species was the highest (10 species) in Bioreactor B when compared to the other bioreactors (Bioreactor A, C, D, and E). Proteobacteria phylum (9 species) was found dominated throughout the study, suggesting that the combination MM with granular activated carbon (GAC) and plastic media encouraged the growth of various bacterial species that were resistant to high-levels of PCP and thus enhancing the removal of PCP. It can be concluded that the hybrid treatment system of multimedia (MM) and SBBR is highly capable of removing PCP from water contaminated with PCP due to the diversity presence of PCP resistant bacteria in this bioreactor. MM-SBBR could be the effective treatment method for wastewater containing PCP to improve water quality and ensure sustainability. Graphical abstract: Unlabelled Image Highlights: Multimedia–sequencing batch biofilm reactor (MM-SBBR) was able to remove pentachlorophenol (PCP). The MM-SBBR attained high removal of COD (97%), NH3 -N (93%) and PCP (99%). Proteobacteria was the main phylotypes presence in the MM-SBBR. MM-SBBR enhanced the growth of bacteria and increased PCP removal. MM-SBBR can be a good option for the effluent treatment with high loads of PCP.